The THE CORRELATION BETWEEN LIFESTYLE AND HYPERTENSION INCIDENCE ON THE ELDERLY - muhammad sowwam muhammad sowwam; kunaryanti; Septia Nalinda; Danik Dwiyanti; Eny (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Background: Indonesia has a prevalence of hypertension that continues to increase annually. This high incidence is in line with the increasing life expectancy (UHH) both nationally and globally. Hypertension can be caused by an unhealthy lifestyle. Aim: To analyze the correlation between lifestyle and the incidence of hypertension in the elderly in Dukuh Mokolegi, Celep Village, Kedawung, Sragen.Method: This is a correlational analytic study with a cross-sectional approach. The sample in this study amounted to 41 people. The sample was taken using a total sampling technique. The results of the study were tested using the Pearson statistical test with a significance level of α = <0.05. The research instrument used a lifestyle questionnaire and hypertension measurement with a sphygmomanometer. This study was conducted in Dukuh Mokolegi, Celep Village, Kedawung, Sragen. Results: The results of the Pearson correlation test with an error level (α) = 0.05 obtained a p-value of 0.002 with a correlation strength of -0.468. This indicates a significant relationship between lifestyle and the incidence of hypertension. Conclusion: A better lifestyle is more likely to prevent hypertension in the elderly. Keywords: Lifestyle, Hypertension, Elderly